Here v1=k*r1 , v2=k*r2 , v3=k*r3 therefore v1:v2:v3=r1:r2:r3 but how is v1:v2:v3=r3:r2:r1

Asked by Alekhya K | 7th Oct, 2014, 11:48: AM

Expert Answer:

Dear alekhya.kunchakara@gmail.com

Thanks for asking us a question in Ask the Expert section of TopperLearning.com.

The answer has been updated. Kindly revert back if you have any boubt.
Regards

Topperlearning Team.

Answered by Priyanka Kumbhar | 7th Oct, 2014, 03:17: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.